Hittite Lexicographic Studies, 1 - Hoffner, Harry A. Jr. (Fs Finkelstein)
ekt- ‘hunting-net’; ḫueša- ‘distaff’; ḫupp-, ḫuwapp-; maišta- ‘strand of yarn’; panzakitti- ‘roping(?)’; šemeḫuna (a foodstuff); anda šekuwa-; tarna- ‘skull’; tarašna- ‘throat’.